2021
DOI: 10.1186/s13017-021-00398-5
|View full text |Cite
|
Sign up to set email alerts
|

Periappendiceal fat-stranding models for discriminating between complicated and uncomplicated acute appendicitis: a diagnostic and validation study

Abstract: Background Recent studies have reported promising outcomes of non-operative treatment for uncomplicated appendicitis; however, the preoperative prediction of complicated appendicitis is challenging. We developed models by incorporating fat stranding (FS), which is commonly observed in perforated appendicitis. Material and methods We reviewed the data of 402 consecutive patients with confirmed acute appendicitis from our prospective registry. Multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 64 publications
2
4
0
Order By: Relevance
“…According to the multivariate analysis in our study, it was confirmed that patients with a higher appendiceal diameter (greater than 6 mm), appendicolith, and peritonitis were significantly associated with ACA, while patients who were older and had target sign appearance were less likely to suffer from ACA. Our data are in agreement with the results of previously published studies [ 33 , 34 ]. However, the existence of an appendicolith can be observed in both normal and abnormal appendices, and it remains controversial whether an appendicolith leads to an increased risk of appendicitis [ 35 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…According to the multivariate analysis in our study, it was confirmed that patients with a higher appendiceal diameter (greater than 6 mm), appendicolith, and peritonitis were significantly associated with ACA, while patients who were older and had target sign appearance were less likely to suffer from ACA. Our data are in agreement with the results of previously published studies [ 33 , 34 ]. However, the existence of an appendicolith can be observed in both normal and abnormal appendices, and it remains controversial whether an appendicolith leads to an increased risk of appendicitis [ 35 ].…”
Section: Discussionsupporting
confidence: 94%
“…Another interesting finding of our study was the association of the presence of free intraperitoneal fluid in patients with ACA, mainly in its diffuse form or in a periappendiceal location, as determined by our univariate analysis, which is also supported by reports in the literature [ 33 , 34 , 39 ]. Although the present finding was not evaluated as satisfactory in our multivariate analysis, possibly due to the number of patients in our study, further research is needed to conclude if the location of fluid is correlated with ACA or if it is a finding that is not associated with children with a clinical picture of AA.…”
Section: Discussionsupporting
confidence: 89%
“…Clinically, acute appendicitis is classi ed as either complicated appendicitis or uncomplicated appendicitis [1]. However, it is often di cult to preoperatively determine the most appropriate management for acute appendicitis, such as emergency appendectomy (EA), interval appendectomy (IA), or repeating nonoperative management (NOM) [2]. In the present study, we considered the treatment strategy for acute appendicitis from the following three perspectives: prediction of which patients should avoid emergency surgery, prevention of failure of IA or NOM, and a malignant tumor as the etiology of the appendicitis.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, acute appendicitis is classified as either complicated appendicitis or uncomplicated appendicitis [ 1 ]. However, it is often difficult to preoperatively determine the most appropriate management for acute appendicitis, such as emergency appendectomy (EA), interval appendectomy (IA), or repeating nonoperative management (NOM) [ 2 ]. In the present study, we considered the treatment strategy for acute appendicitis from the following three perspectives: prediction of which patients should avoid emergency surgery, prevention of failure of IA or NOM, and a malignant tumor as the etiology of the appendicitis.…”
Section: Introductionmentioning
confidence: 99%